ADMINISTRATIVE FACTORS AFFECTING THE EFFECTIVENESS OF ACADEMIC AFFAIRS ADMINISTRATION IN PRIVATE SCHOOLS UNDER SAKON NAKHON PROVINCIAL EDUCATION OFFICE - Chaisura, Nittaya; Pheasa, Akkaluck; Chalakbang, Wannika (Journal of Graduate School Sakon Nakhon Rajabhat University, 2024)
The purposes of this research were to 1) examine the level of administrative factors in private schools under the Sakon Nakhon Provincial Education Office (SNK-PEO), 2) examine the level of effectiveness of academic affairs administration in private schools, 3) explore the relationship between administrative factors and the effectiveness of academic affairs administration in private schools, 4) determine predictive power of administrative factors affecting the effectiveness of academic affairs administration in private schools, and 5) establish guidelines for developing administrative factors affecting the effectiveness of academic affairs administration in private schools. The sample, obtained through stratified random sampling, consisted of school administrators, teachers in charge of academic affairs, and teachers in private schools under the SNK-PEO in the academic year 2020, yielding a total of 283 participants. The research instrument for data collection was a set of 5-level rating scale questionnaires with two aspects: Aspect 1- Administrative Factors in Private Schools, with IOC values ranging between .80 and 1.00, the discriminative power value ranging from .34 to .68 and the reliability value of .97, and Aspect 2: Effectiveness of Academic Affairs Administration in Private Schools with IOC values ranging from .80 to 1.00, the discriminative power value between .31 and .65 and the reliability value of .94. The statistics for data analysis included frequency, percentage, mean, standard deviation, Pearson’s product-moment correlation coefficient and stepwise multiple regression analysis. The findings were as follows: 1) The administrative factors in private schools under the SNK-PEO as a whole were at a high level, 2) The effectiveness of academic affairs administration in private schools under the SNK-PEO as a whole was at a high level, 3) The administrative factors and the effectiveness of academic affairs administration in private schools under the SNK-PEO had a positive relationship at the .01 level of significance, 4) The four aspects of administrative factors affecting the effectiveness of academic affairs administration in private schools under the SNK-PEO were able to predict private schools’ effectiveness at the .01 level of significance. The said factors, including budget (X3), building (X5), heads of academic affairs department (X1), and teachers (X2), achieved a correlation coefficient of .741 and a predictive power of 57 percent. The regression equation of raw scores and standardized scores could be written as follows: Y' = 1.372 + .168(X3) + .208(X5) + .169(X1) + .147(X2), Z' = .249(Z3) + .336(Z5) + .167(Z1) + .158(Z2), and 5) The guidelines for developing administrative factors in private schools under the SNK-PEO involved four aspects needing improvement: School administrators, teachers, budget, and building.